Perbedaan Luaran Maternal dan Perinatal pada Ibu Bersalin Usia Reproduksi Sehat dan Usia Berisiko - Wahyuni, Seri; Riyanti, Riyanti (Politeknik Kesehatan Tanjungkarang, 2018)
The old age mother has a risk to get a complication in pregnancy and parturition much higher than reproductive age mother. According to Yensi study (2015), that of the 226 women giving birth over the age of 35 years, as many as 125 people (55.3%) had a history of abnormal pregnancy. In addition, most of the type of labor is by Sectio Caesarea (SC) a total of 119 (51.7%) and suffered complications as much as 44.7%. This study was to identify differences in maternal and perinatal outcomes between healthy reproductive age and risky age maternal in Cempaka Room, Doctor Doris Sylvanus Regional Public Hospital, Palangkaraya. The study design was case-control, data retrieved by conducting interviews at birth mothers in the Cempaka room dr. Doris Sylvanus Palangkaraya. The research sample consisted of 30 samples of mothers of reproductive age (20-35 years) and 30 samples of old-risk maternal age (>35 years). The Data were taken from September to November 2016. Data were analyzed by Chi-Square, Odds ratio, and logistic regression analysis. The results showed that birth weight babies in reproductive age maternal different from risky age maternal (OR=7, 95% CI=1.4 to 35.5). This means that the risky age maternal has seven times greater to give birth a baby with body weight <2500 g or >4000 g. While maternal and perinatal outcomes on the kind of labor, bleeding, gestation, and asphyxia no difference. The difference of perinatal outcomes in the maternal reproductive age between healthy reproductive age and risky age maternal was of infant birth weight. It was recommended that pregnant women and maternity in the age range of 20-35 years.